The priority of liver resection compared with transarterial chemoembolization in hepatocellular carcinoma at BCLC B1 stage: A single-center experience - Yi, Peng-Sheng; Liu, Jun-Ning; Li, Yong; Wu, Bin; Li, Jian-Shui (Frontiers in Surgery, 2022)
Background: This study aims to compare the efficacy of liver resection (LR) and transarterial chemoembolization (TACE) in the treatment of Barcelona Clinic Liver Cancer B1 (BCLC B1) hepatocellular carcinoma. Methods: A total of 65 patients with BCLC B1 were divided into the radical (LR group) and TACE group. Survival analysis was performed using the Kaplan– Meier method. Univariate and multivariate analyses were carried out, and the prognostic factors for survival outcomes were identified using Cox proportional analysis. Results: The 1-, 3-, and 5-year survival rates and the 1-, 3-, and 5- year progression-free survival rates in the LR group (P = 0.036) were significantly higher than those in the TACE group (P = 0.027). Results of the multivariate analysis demonstrated that tumor distribution (both lobes vs. semi- liver) and treatment strategy (LR vs. TACE) were independent risk factors for the over survival (OS) (hazard ratios (HRs): 3.926 and 0.479; P < 0.05) and progression-free survival (PFS) (HR: 3.336 and 0.465, P < 0.05). LR was associated with increased OS and PFS compared with TACE in patients with BCLC B1 hepatocellular carcinoma.